2018
DOI: 10.3389/fmolb.2018.00075
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular ATP Regulates CD73 and ABCC6 Expression in HepG2 Cells

Abstract: The ATP-binding cassette sub-family C member 6 transporter (ABCC6) is an ATP dependent transporter mainly found in the basolateral plasma membrane of hepatic and kidney cells. Mutations in ABCC6 gene were associated to the Pseudoxanthoma elasticum (PXE), an autosomal recessive disease characterized by a progressive ectopic calcification of elastic fibers in dermal, ocular, and vascular tissues. It is reported that the over-expression of ABCC6 in HEK293 cells results in the cellular efflux of ATP and other nucl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 29 publications
5
20
0
Order By: Relevance
“…In probenecid-treated HepG2 cells, we observed an almost complete lack of filopodia, or, if present, they were very short ( Figure 5B, stars) compared to the control cells ( Figure 5A, arrows); as observed in the Abcc6-shRNA cells, the addition of ATP ( Figure 5C, arrows) or adenosine ( Figure 5D, arrows) restored the normal architecture of filipodia. Previously, we showed that ATP as well as adenosine reverted the effect of probenecid on the downregulation of the protein level of CD73, restoring its protein level to that of the control conditions and even above [18]. The finding that adenosine alone mimicked the effect of ATP in this experiment suggests that the ability of ATP to revert the effect of probenecid on cytoskeleton architecture is likely dependent on its ability to be finally transformed in adenosine by CD73.…”
Section: Probenecid Induces Cytoskeletal Rearrangement Of Hepg2 Cellssupporting
confidence: 61%
See 4 more Smart Citations
“…In probenecid-treated HepG2 cells, we observed an almost complete lack of filopodia, or, if present, they were very short ( Figure 5B, stars) compared to the control cells ( Figure 5A, arrows); as observed in the Abcc6-shRNA cells, the addition of ATP ( Figure 5C, arrows) or adenosine ( Figure 5D, arrows) restored the normal architecture of filipodia. Previously, we showed that ATP as well as adenosine reverted the effect of probenecid on the downregulation of the protein level of CD73, restoring its protein level to that of the control conditions and even above [18]. The finding that adenosine alone mimicked the effect of ATP in this experiment suggests that the ability of ATP to revert the effect of probenecid on cytoskeleton architecture is likely dependent on its ability to be finally transformed in adenosine by CD73.…”
Section: Probenecid Induces Cytoskeletal Rearrangement Of Hepg2 Cellssupporting
confidence: 61%
“…CD73 is considered a key regulator in some cancer processes such as drug resistance, tumor metastasis, and tumor angiogenesis [12,13], therefore is an excellent candidate for cancer therapy [14][15][16]. In previous studies, we have reported that knockdown of Abcc6 in hepatocarcinoma cancer cells (HepG2), or the inhibition of its activity lead to the downregulation of NT5E gene, which codifies for the CD73 protein [17][18][19]. Taken together, these data suggest a close correlation between ABCC6 and CD73.…”
Section: Introductionmentioning
confidence: 66%
See 3 more Smart Citations